2013
DOI: 10.1088/0029-5515/53/3/033009
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of out-vessel magnetic diagnostics for plasma boundary reconstruction in tokamaks

Abstract: Abstract.To improve the low frequency spectrum of magnetic field measurements of future tokamak reactors such as ITER, several steady state magnetic sensor technologies have been considered. For all the studied technologies it is always advantageous to place the sensors outside the vacuum vessel and as far away from the reactor core to minimize radiation damage and temperature effects, but not so far as to compromise the accuracy of the equilibrium reconstruction.We have studied to what extent increasing the d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…A detailed study has been performed for optimization of magnetic probe arrays inside and outside the vacuum vessel. It was found that these two magnetic probe arrays are essential for equilibrium reconstruction during a plasma current ramp as currents are induced in the vacuum vessel [17].…”
Section: Introductionmentioning
confidence: 99%
“…A detailed study has been performed for optimization of magnetic probe arrays inside and outside the vacuum vessel. It was found that these two magnetic probe arrays are essential for equilibrium reconstruction during a plasma current ramp as currents are induced in the vacuum vessel [17].…”
Section: Introductionmentioning
confidence: 99%
“…δ ij is the Kronecker delta function. We note that Gaussian processes have been introduced to the fusion community with a non-parametric tomography for the JET FIR interferometer data [5] and used for current tomography [6,7,43,44], beam emission spectroscopy [10,11], soft x-ray spectroscopy [12], x-ray imaging crystal spectroscopy [14] and profile regressions [32]. In this work, Gaussian processes are used to model electron temperature and density profiles to constrain their smoothness (gradient scale length) without imposing any specific profile shapes or assumptions such as monotonicity.…”
Section: Gaussian Process Priormentioning
confidence: 99%
“…(18), and N pixel is the total number of CCD pixels for the i th channel.Σ is an N pixel × N pixel square diagonal matrix containing variances of the measured signal at each pixel of the CCD camera as iň…”
Section: Interference Filter and Instrument Functionsmentioning
confidence: 99%